Hope this helps you out :D
It’s 2 equations so in order to solve the previous system, you can use different methods, as for example substitution or addition of equations. In this case, you use the second one, due to the fact you have 7x in one equation and -7x in the other equation. In this way you can easily eliminate variable x and then solve for y. With the value of y you can replace in any of the two equations and solve for x.
7x-y=-1
-7x+3y=-25
Summarizing, you proceed as follow:
- add up the given equations
7x - y = -1
-7x+3y=-25
——————
0 +2y=-26
- solve for y in the previous equation
2y=-26
y=-26/2
y=-13
- replace the obtained value of y in one of the given equations, and solve for x
7x-(-13)=-1
7x+13=-1
7x=-1-13
7x=-14
x=-14
x=-14/7
x=-2
Hence, the solution of the given systems of equation is:
X=-2
Y=-13
Answer:
8 - 8 = 0 , 8 * 5 / 4 = 10 , 8 * 4 - 8 = 24
Step-by-step explanation:
8 - 8 = 0
8 * 5 = 40 / 4 = 10
8 * 4 = 32 - 8 = 24
Answer:
ans is mean
Step-by-step explanation:
pls make me brainlest pls i beg you
Answer:
Step-by-step explanation:
Multiply the first term by , the second term by , the third term by .
<u>The first term becomes:</u>
<u>The second term becomes:</u>
<u>The third term becomes:</u>
<u>Their sum is:</u>
Correct choice is B